The influence of process parameters on the chemical and structural properties of solution combustion prepared vanadium pentoxide - Yilmaz, Esma; Sonmez, M. Seref (Elsevier BV, 2020)
Abstract The present study shows the effects of the process parameters on the combustion synthesised’ powder properties using a systematic design of experiments. It describes the fabrication of high purity V2O5 powders with the manipulation of fuel types and fuel-to-oxidizer ratios. Additionally, for the first time the mixture of fuels was used to demonstrate clearly the role of the fuel on the powder properties. Flame temperature of the reaction was calculated for each parameter to understand how the reaction kinetics affect the powder properties especially primary particle size and morphology. Correlation between the physical and chemical properties of the powders and the precursor’s condition was successfully built.